Managing Ghost Workers Fraud on Payroll in Tanzania: A Conceptual Framework - Tefurukwa, O.W. (Research Center for Governance and Public Policy Department of Public Administration University of Sri Jayewardenepura, Sri Lanka, 2021)
Tanzania has made several reforms to improve public service since independence in 1961. One of the major concerns has been to wipe out ghost workers on the payroll. The efforts would improve public service and avoid unnecessary wastages of resources. For decades the payroll still bears names of fictitious and ex-employees who either retired or deceased. Ghost workers have been oozing scarce funds that could support service to the neediest Tanzanians. The situation calls for immediate but comprehensive interventions for dealing with menace to avoid further negative impacts on public service management and the country. The core intervention is to comprehend the nature of fraud on the payroll in Tanzania. Therefore, the paper proposes a conceptual framework for identifying and managing ghost workers on the payroll. The study is based on secondary data. The study used Fraud Triangle Theory, Fraud Diamond Theory, and Fraud Lifecycle Management Theory to construct the conceptual framework for managing ghost workers on the payroll in Tanzania. The framework can facilitate organizations, researchers, and human resources practitioners to analyze initial motives and traits of employees towards unethical behaviors, the probability of fraud on the payroll, and the quality of fraud management systems. In addition, the framework portrays that the fraud management systems must be inherent features of efficient and effective human resources management of any organization that needs and wants to curb ghost worker frauds on the payroll.
Keywords: Ghost Worker Frauds, Fraud Management, Conceptual Framework, Human Capital Management Information System, Payroll